180k views
1 vote
What is f(3) if f(x) = - 4x+1 ?

A.-44
B.-11
C. 1/2
D. 13

Please help me! :/

User Mcmlxxxiii
by
4.9k points

1 Answer

6 votes

Answer:

Here is the equation:

f(x)=4x+1f(x)=4x+1

You need to find f(3). To do that, substitute all the x's with 3:

f(x)=4x+1 \rightarrow f(3)=4\times3 + 1f(x)=4x+1→f(3)=4×3+1

The first thing you need to do is multiply 4 by 3. Multiply:

4 \times 3 = 124×3=12

Here is your new equation:

f(3)=12+1f(3)=12+1

To get your answer, you need to add 12 and 1. Add:

12+1 = 1312+1=13

That means:

\bf f(3)=13f(3)=13

Explanation:

13 is the ans

User Vvlevchenko
by
4.6k points